Personality and Coping among Turkish College Students: A Canonical Correlation Analysis - (:unkn) unknown (EDAM, 2010)
The discussion about whether coping strategies are determined by stable characteristics of the individual, such as personality or they are determined by situation-specific variables, such as cognitive appraisals regarding stressful situation is still in agenda. Thus, the relationship between coping and personality traits was examined with 237 students (53.2 % male; mean age = 22.22 years old) who were enrolled in classes at Marmara University in Istanbul, Turkey. The participants responded to the Ways of Coping with Stress Scale (WCSS) and the NEO Five Factor Inventory (NEO-FFI). The canonical correlation analysis showed that those who were high in conscientiousness tend to use more self-confident, optimistic, and turning to religion coping strategies whereas those who were high in extraversion were more likely to use self-confident and seeking of social support strategies in stressful situations.
Keywords: Personality; Coping; NEO Five Factor Inventory; Canonical Correlation Analysis; GENDER-DIFFERENCES; COGNITIVE APPRAISALS; 5-FACTOR MODEL; STRESS; STYLES; NEUROTICISM; TRAITS; EXTROVERSION; METAANALYSIS; ADOLESCENTS